PENDIDIKAN ANTI KORUPSI DALAM PERSPEKTIF PENDIDIKAN PESANTREN - Budiono Budiono (LP3M Sekolah Tinggi Agama Islam Ma'arif Magetan, 2021)
Islamic boarding schools as religious institutions can be part of a good anti-corruption movement. However, its effectiveness may still be questioned. In Islamic boarding schools, for example, the kiai as the patron of the community can be used as pressure for the bureaucracy to reduce corrupt practices. However, what the kiai do can only be done within the boundaries of a cultural movement. That is, they can make moral appeals so that people avoid corrupt behavior.Keyword : anti-corruption, Islamic boarding schools, religious.